The Current Situation and Influencing Factors of Job Stress Among Frontline Nurses Assisting in Wuhan in Fighting COVID-19 - Zhan, Yu f.; Ma, Shuang; Jian, Xiang d.; Cao, Ying j.; Zhan, Xiao q. (Frontiers in Public Health, 2020)
Background: The coronavirus disease 2019 (COVID-19) pandemic continues to pose an unprecedented threat and challenge to public health around the world. Lacking sufficient human resources, nurses are required to undertake an increased workload at the clinical front-line of this epidemic. Additionally, nurses are at a high risk due to their working within close proximity to COVID-19 patients. As a result, they experience increased job stress. Objective: To explore the current situation and influencing factors of job stress among clinical first-line nurses fighting COVID-19. Methods: A convenience sampling method was used to conduct a questionnaire survey with 110 nurses who were on the clinical front-line of the COVID-19 epidemic in a hospital in Wuhan. Results: The job stress scores of clinical nurses on the front-line of the COVID-19 epidemic were collected (91.42±26.09), in which the dimensions of work environment and resources, and workload and time pressure were ranked first and second, respectively. The results of a multiple stepwise regression analysis showed that working hours per day, service years, number of night shifts per week, and level of academic qualification were the main factors affecting the job stress levels of nursing staff. Conclusions: The job stress of nurses on the clinical front-line of the COVID-19 epidemic were found to be at a medium level. Nursing leaders and hospital managers should pay attention to the impact of job stress on front-line nurses, while taking positive and effective measures aimed at eliminating the source of nursing work pressures, so as to stabilize their nursing teams and promote their work in the fight against this epidemic.